The ‘Matthew effect’ in Chinese kindergarten principals’ professional development: a mixed-methods study - Qian, Yu; Zhangchen, Shiyuan; Li, Hui (Frontiers in Psychology, 2023)
Principals play a leading role in kindergarten quality improvement, and thus their needs for professional development (PD) should be met. This national study adopted a mixed-methods approach to survey 3,065 kindergarten principals in China and interviewed 16. First, the latent profile analysis yielded three profiles of PD needs: (1) low (7.5%), (2) medium (22.2%), and (3) high profiles (70.3%), indicating 70.3% of Chinese principals need PD badly. The high profile group features ‘inexperienced principals working at newly established private kindergartens', the most disadvantaged among the three groups. Second, ANOVA tests revealed significant rural-urban and public-private differences in Chinese principals’ professional backgrounds and PD needs. Third, the follow-up interviews confirmed remarkable rural-urban and public-private gaps in PD needs, indicating a noticeable ‘Matthew effect': the poor got less, whereas the rich got more. The implications for future PD policy and program design are discussed.